On the Generalized Power Transformation of left Truncated Normal Distribution (Global Journal of Science Frontier Research, 2021)
The purpose of this study is to establish a unified approach to the transformation problems of certain type of random variable and their associated probability density functions in the generalized setting. The results presented in this research, trivialized the results obtained by several researchers in the literature, in particular for a random variable that follows a lefttruncated normal distribution.
Keywords: truncated distribution; normal distribution; transformation; moments